2020
DOI: 10.24996/ijs.2020.61.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Levels of Metabolic Hormones and Lipid Profile in Growth Hormone Deficient Patients

Abstract: Abstract The current study aims to evaluate levels of metabolic hormones and lipid profile in a sample of growth hormone (GH) deficient patients. Seventy five GH deficient patients and twenty healthy subjects used as control group have been participated in this study during their attendance to the National Diabetic Center for Treatment and Research/Al-Mustansiriya University. The studied subjects’ ages were with a range (3-15 years). Blood samples were collected from the studied subjects to determine lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The demand of lipid profile test by healthcare in the clinical practice is important as it reflects the results for diagnostic purposes [10]. Patients with growth hormone deficiency (GHD) showed a tendency of instabilities in lipid profile [11]. Also, another study revealed that the parasitic infections such as T. gondii, has a role in changing the lower cholesterol, triglycerides and LDL levels, while increasing HDL level [12].…”
Section: Introductionmentioning
confidence: 99%
“…The demand of lipid profile test by healthcare in the clinical practice is important as it reflects the results for diagnostic purposes [10]. Patients with growth hormone deficiency (GHD) showed a tendency of instabilities in lipid profile [11]. Also, another study revealed that the parasitic infections such as T. gondii, has a role in changing the lower cholesterol, triglycerides and LDL levels, while increasing HDL level [12].…”
Section: Introductionmentioning
confidence: 99%
“…Growth hormone (GH), which is a polypeptide hormone that is released by the anterior pituitary gland, is the main regulator of statutory growth during childhood and adolescence 1 . Growth hormone largely affects growth and development by activating the processes through insulin-like growth factor-1 (IGF-1) 2 .…”
Section: Introductionmentioning
confidence: 99%